Estimation of an Object Trajectory in an Intake Duct using Numerical Simulation - Aravinth, L.; Vidhyashankar, N.; Abbas, Reza; Sudharsan, Natteri M. (Defence Science Journal, 2020)
This research aims to study the trajectory of an object inside a serpentine duct of a gas turbine engine using computational fluid dynamics. The coupled implicit solver with 6-degree of freedom (6-DOF) and chimera mesh (Overset mesh) is used to track the object’s trajectory. Various object orientation and aircraft angle of attack (AoA) at a speed of Mach 0.3 is studied. This provides an understanding of the bird’s movement inside the duct that might cause damage to the engine components during takeoff and landing. It was observed that the combination of AoA and object orientation decide the length of the trajectory before impact. The object is found to travel the farther when the AoA is at -20o with object oriented at 0o and 45o.The object tends pitch and yield to the flow irrespective of its initial orientation and hence the aircraft angle of attack is a more predominant factor. The effect of pressure recovery due to AoA and object orientation is also presented. The recovery is found to be at its best for AoA of 0o irrespective of object orientation. This approach could be utilised for designing an intake duct that can limit the damage to engine components due to bird ingestion and simultaneously maintain good pressure recovery.